Circadian Rhythms and Breast Cancer: The Role of Per2 in Doxorubicin-Induced Cell Death - Megan I. Mitchell; Anna-Mart Engelbrecht (Journal of Toxicology)
Mammalian circadian rhythms form an integral physiological system allowing for the synchronisation of all metabolic processes to daily light/dark cycles, thereby optimising their efficacy. Circadian disruptions have been implicated in the onset and progression of various cancers, including those arising in the breast. Several links between the circadian protein Per2 and DNA damage responses exist. Aberrant Per2 expression results in potent downstream effects on both cell cycle and apoptotic targets, suggestive of a tumour suppressive role for Per2. Due to the severe dose limiting side effects associated with current chemotherapeutic strategies, including the use of doxorubicin, a need for more effective adjuvant therapies to increase cancer cell susceptibility has arisen. This study was therefore aimed at characterizing the role of Per2 in normal breast epithelia (MCF-12A) and in ER− breast cancer cells (MDA-MB-231) and also at determining the role of Per2 in doxorubicin-induced cell death. In both cell lines Per2 protein expression displayed a 24-hour circadian rhythm in both cell lines. Per2 was located predominantly in the cytoplasm, with nuclear localization observed with lower cytoplasmic fluorescent intensities. Our results show that Per2 silencing effectively sensitizes the chemoresistant MDA-MB-231 breast cancer cells to the cytotoxic effects of doxorubicin.